Validasi Metode Penentuan Mn Dalam Oli Lubrikan Dengan Metode Pengenceran Langsung Menggunakan Spektrofotometer Serapan Atom - Napitupulu, Rona Maningting; Julia, Dirgarini; Panggabean, Aman S. (Indonesian Journal of Chemical Research, 2019)
Validation method on the determination of Mn in lubricating oil by direct dilution method using Atomic Absorption Spectrophotometer (AAS) in Laboratory & Environment Control PT. Badak NGL Bontang has been done The validation method was done with research stages such as determination of optimum solvent, and determination of some important parameters influential for validation method such as parameter of liniearitas (r), Instrument Detection Limit (IDL), Methode Detection Limit (MDL), accuracy, precision, Limit of Detection(LOD) and Limit of Quantitation(LOQ). The result of research obtain is good, showed that the linearity value with R2 â‰¥ 0,997. The IDL and MDL value was 0.0021 ppm and 0.0092 ppm respectively and has been acceptability requirements of MDL. The accuracy paramater obtained recovery value with range 82.25-88.34%. The measurement of repeatability and reproducibility, the CV Horwitz value smaller than % RSD, indicating the method had a good precision. The measurement of LOD and LOQ value was 0.095 ppm 0.317 ppm respectively. Based on the result of the research determination method of Mn in lubricating oil by direct dilution method using AAS concluded valid.